Portrait of Henricus Liberti: A Musical Painting by Anthony Van Dyck (1599-1641) - De Paepe, Timothy 1981-; Van Cauteren, Katharina (Veurne Hannibal Books, 2022)
The Antwerp Baroque portrait specialist Anthony Van Dyck painted Henricus Liberti in around 1627-1632 as a self-assured and talented musician, who was well aware of his worth. Today, just a handful of Liberti's musical pieces have been preserved and the archives hardly mention any traces of the life of this Antwerp keyboard virtuoso and composer. We do not even know for sure when and where he was born. The fact that the musician was not forgotten is largely due to Van Dycks magnificent Portrait of Henricus Liberti, which is now part of The Phoebus Foundations collection. This Phoebus Focus zooms in on the prestigious history of Van Dycks portrait and brings together the details of Liberti's life and oeuvre. We also focus on the masterly way in which the painter depicted the inspired virtuoso.
Keywords: Liberti, Henricus -- 1600-1669; Van Dyck, Anthony -- 1599-1641; 17th Century (1601-1700); Fine art